Mudança estrutural e competitividade das exportaç\~oes brasileiras: Uma vis\~ao de longo prazo - Marcelo José Braga Nonnenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The purpose of the paper is to analyze Brazilian exports data between 1962 and 2016 by industries, verifying if the export structure has been modified in recent years towards a pattern more concentrated in primary products, due to a loss of competitiveness. Brazilian exports have been analyzed between these years by six industries. It has been utilized the Constant Market Share methodology in order to identify a change in competitiveness. The main conclusion is that competitiveness has increased in initial years, due to subsidies and government incentives to more technology intensive industries and also in the period of more intense trade openness. And the two more technology intensive industries, namely Machines and Equipment and Other Industries have seen a competitiveness loss in the final years. Therefore, changes in competitiveness seem to be strongly correlated with changes in manufacturing structure and industrial policies.
Keywords: F14; 330; export concentration in primary goods; competitiveness; Brazilian exports; constant market share